PENERAPAN MODEL TREFFINGER TERHADAP HASIL BELAJAR IPA KELAS IV SD NEGERI 54 LUBUKLINGGAU - Sumiati, Sumiati; Satinem, Yohana; Yuneti, Armi (Unversitas Katolik Santo Thomas, 2022)
The research aimed that to determine the completion of science learning outcomes for fourth grade students of SD Negeri 54 Lubuklinggau. The method of this research was a quasi-experimental. The population was all fourth grade students of SD Negeri 54 Lubuklinggau, totaling 20 students. The data was collected by using saturated sampling technique. The collected data was analyzed using tests. Based on the data analysis of a confidence level was = 5% and dk = 19 shows large = 42,39 and = 1.64. Thus, it can be concluded that the fourth grade science learning outcomes of SD Negeri 54 Lubuklinggau after the appliation of the significant treffinger learning model have been completed. The average of the student’s final test was 20 students.